Migration of Moroccan Companies: An Attempt to Model Marketing Policy - Hamid Nechad; Abdelghani Lebbar; Meryeme Bahha (Migration Letters, 2023)
Several factors influence the decisions of Moroccan companies wishing to set up in the rest of the world, particularly in Africa. Parameters such as political stability, Sahelian terrorism, and proximity to the regimes in place could constitute variables of great importance. This contribution attempts to define the important elements in terms of decision-making, taking into account the current context. The research model is based on J.H. Dunning’s ESP (Environment, System and Policies) paradigm, which focuses on the country-specific advantages that make it possible to choose a host country for investment. This article proposes to introduce variables that are linked to the reality of sub-Saharan Africa: political stability, the threat of jihadists and domestic stability. The empirical results of the questionnaire study show a positive, but not statistically significant, correlation between these variables and location decisions. This underlines the importance of further research to better understand the strategic decision-making process in this complex context.